Alexander Kushner in Dialogue with Alexander Pushkin - Sadzińska, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
Alexander Kushner’s poetry is an endless and timeless dialogue with his predecessors. Alexander Pushkin has a special place among them. Overt and covert references to the author of Eugene Onegin are present at various levels of Kushner’s texts – in themes, images, ideas, as well as at the level of formal organization: in language and metrics. The present article deals with the modes of reception and interpretation of Pushkin’s lyrics in the oeuvre of the contemporary poet from St. Petersburg. The analysis focuses on the varied forms of Kushner’s intertextual dialogue with the Romantic poet (quotations, allusions, reminiscences, references both of literary and biographical character). The sources and nature of reminiscences from Pushkin are indicated, such as accepting dialogue, polemics, assimilation, rejection and partial redefinition.